2017
DOI: 10.1287/mnsc.2015.2406
|View full text |Cite
|
Sign up to set email alerts
|

Battle of the Channels: The Impact of Tablets on Digital Commerce

Kaiquan Xu,
Jason Chan,
Anindya Ghose
et al.

Abstract: T he introduction of tablets in online retailing has created an additional touchpoint through which e-commerce firms can interact with consumers. In this paper, we seek to understand and measure the causal impact of tablets on e-commerce sales. In doing so, we examine the complementary and substitution impact of the tablet channel on the smartphone and PC channels. We rely on a unique data set from Alibaba, the largest e-commerce firm in the world, and exploit a natural experiment via the iPad app introduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
117
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(128 citation statements)
references
References 45 publications
7
117
0
Order By: Relevance
“…Although many studies in the marketing modeling literature investigating the implications of mobile platforms have emerged, [37][38][39][40] our knowledge regarding the consumption psychology of smartphone use is very limited. 6 Moreover, while recent studies have shown that various interfaces may affect the willingness to pay, 10 preferences for affect-laden food, 11 information-processing difficulty, 39 and even decisionmaking processes, 12 research considering smartphones a holistic concept is limited, and further research could allow us to better understand how devices shape our minds.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies in the marketing modeling literature investigating the implications of mobile platforms have emerged, [37][38][39][40] our knowledge regarding the consumption psychology of smartphone use is very limited. 6 Moreover, while recent studies have shown that various interfaces may affect the willingness to pay, 10 preferences for affect-laden food, 11 information-processing difficulty, 39 and even decisionmaking processes, 12 research considering smartphones a holistic concept is limited, and further research could allow us to better understand how devices shape our minds.…”
Section: Discussionmentioning
confidence: 99%
“…For example, holding a resume attached to a heavy clipboard leads people to think the job candidate as more important [4]. Incidental exposure to the haptic sensation of roughness (vs. smoothness) increases individuals' attention to the unfortunate others and promotes charitable behavior [35]. The current research seeks to add to this line of research by proposing that haptic experiences obtained from interacting with devices can affect consumers' haptic judgment on products displayed in the digital environment.…”
Section: Haptic Perception and Digital Technologymentioning
confidence: 99%
“…For example, it has been found that reaching out to touch a product on a touchscreen device can make the consumption experience more vivid in people's mind and thus lead to higher purchase intention as opposed to using a mouse to click on the product [32]. Furthermore, touchscreens lead to more impulsive and diversity-seeking purchase behavior [35]. However, scant attention has been paid to mid-air interaction, which has shown great potential in the e-commerce context [13].…”
Section: Introductionmentioning
confidence: 99%
“…For many companies, the mobile internet has become the main growth driver, as the example of Facebook shows (Forbes, ). Mobile devices, however, are fundamentally different from desktop devices; they vary in display sizes (Sohn, Seegebarth, & Moritz, ; Xu, Chan, Ghose, & Han, ), input method (finger vs. mouse and keyboard; Chung, Kramer, & Wong, ), convenience (Clarke, ), and context of use and ubiquity (Forman, Ghose, & Goldfarb, ) and timeliness of information access (Ghose, Goldfarb, & Han, ). Oftentimes, on mobile devices, consumers are presented with additional aids to simplify and speed‐up purchase decision processes, such as pop‐ups, bigger “purchase” buttons or a much stricter funnel towards purchase.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the increasing attention devoted to the effects of the internet on consumer behavior by marketing and information systems literature in the past two decades (Bang, Lee, Han, Hwang, & Ahn, ; Koufaris, ; Schellong, Kemper, & Brettel, ; Xu et al, ), it is not well understood yet, how the consumer decision‐making process and related psychological processes and strategies are impacted by the introduction of the mobile internet. The changed information environment might alter purchase decisions consumers take (Darley et al, ).…”
Section: Introductionmentioning
confidence: 99%